Occupying Paulista: Housing activism, the new right and the politics of public space during the Brazilian crisis. (June 2021) - Albert, Victor
Brazilian society has frequently been described as polarized during the country's recent political and economic crisis. In 2018, a wave of opposition to the centre-left Workers' Party culminated in the election of Jair Bolsonaro, a right-wing populist who portrays the political left as a malevolent force in Brazilian society. In this paper I explore this polarization through drawing on ethnographic research with the Homeless Workers' Movement ( Movimento de Trablhadores Sem-Teto, MTST), a large urban social movement that develops settlements on underutilized land in the city, and a prominent civil society opponent of Bolsonaro. More specifically, I examine a key site of socio-spatial tension in São Paulo, Paulista Avenue, as a new political right came to predominate on the city's main thoroughfare during the campaign to impeach the Workers' Party President, Dilma Rousseff. I show how the perceived intolerance of the mobilized right helped to establish new normative codes that regulated the political symbolism which could be displayed in public spaces. Lastly, I consider how the vilification of the MTST in particular and the political left in general by the new right is embedded in broader structures of stigmatization.